2019
DOI: 10.1149/2.0321902jes
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of Electrochemically-Grown Copper Sulfide Films

Abstract: The electrochemical growth of copper sulfide films on copper has been studied voltammetrically and potentiostatically in 0.1 M sodium chloride solutions containing sulfide concentrations ranging from 10 −4 M to 10 −3 M. The properties of the films formed were investigated using electrochemical impedance spectroscopy. Film growth was observed to occur in two stages: the initial formation of a thin porous base layer at low potentials, followed by film restructuring leading to increased porosity and the depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Although the location of the previously discussed base layer and its apparent thickness are indicated in Figure 8d, they are difficult to observe, owing to the presence of much larger features. The formation of such a thick crystalline outer deposit was consistent with our previous observations [ 6–15 ] and with our demonstration that growth of this deposit occurred at the film/solution interface, supported by the transport through the pores of the base layer of Cu(I), as both sulfide complexes (Cu(SH) 2 − ) and Cu 3 S 3 clusters, formed at the Cu surface. [ 15,24–29 ]…”
Section: Resultssupporting
confidence: 91%
“…Although the location of the previously discussed base layer and its apparent thickness are indicated in Figure 8d, they are difficult to observe, owing to the presence of much larger features. The formation of such a thick crystalline outer deposit was consistent with our previous observations [ 6–15 ] and with our demonstration that growth of this deposit occurred at the film/solution interface, supported by the transport through the pores of the base layer of Cu(I), as both sulfide complexes (Cu(SH) 2 − ) and Cu 3 S 3 clusters, formed at the Cu surface. [ 15,24–29 ]…”
Section: Resultssupporting
confidence: 91%
“…Therefore, the probability of pitting corrosion is most likely low. Separation of the sulfide layer from the Cu substrate confirms that the corroded copper surface is roughened, but not pitted [37]. However, the potentiodynamic polarization curves for copper in deaerated sulfide and chloride containing solutions indicate that copper is passive in a wide potential range and shows passivity breakdown and hysteresis in the current upon reversing the potential sweep after breakdown has occurred.…”
Section: Corrosion Of Coppermentioning
confidence: 85%
“…Once oxygen in the repository is consumed by general corrosion and anaerobic conditions are established, the major concern to the long-term durability of the copper canisters is, thus, corrosion by sulfide induced reactions. Corrosion studies in aqueous solutions containing sulfide ions (SH -) have shown that sulfide corrosion is a two-step process where adsorption on copper surface occurs first to form the chemisorbed species Cu(SH)ads, which leads to deposition of Cu2S on the Cu surface by reaction of the chemisorbed species with Cu and SH - [34]- [37]: Cu + SH -Cu(SH)ads + e -Cu + Cu(SH)ads + SH -Cu2S +H2S + e -Hydrogen evolution under anoxic conditions is the viable cathodic reaction:…”
Section: Corrosion Of Coppermentioning
confidence: 99%
See 2 more Smart Citations